2014
DOI: 10.1517/13543784.2015.974804
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory agents to treat or prevent type 2 diabetes, metabolic syndrome and cardiovascular disease

Abstract: The available data supports the concept that targeting inflammation improves insulin sensitivity and β-cell function; it also ameliorates glucose control in insulin-resistant patients with inflammatory rheumatoid diseases as well in patients with metabolic syndrome or T2DM. Although promising, the observed metabolic effects remain rather modest in most clinical trials. The potential use of combined anti-inflammatory agents targeting both insulin resistance and insulin secretion appears appealing but remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
155
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(160 citation statements)
references
References 180 publications
1
155
1
3
Order By: Relevance
“…TNF was one of the first inflammatory molecules shown to play a role in metabolic disease (211). Targeting this pathway in preclinical models proved successful (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228), although comprehensive human studies are lacking, and the existing limited studies have reported both failures and successes in humans (229). The limitations of the human studies with existing anti-cytokine reagents were recently reviewed in an excellent article (230).…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…TNF was one of the first inflammatory molecules shown to play a role in metabolic disease (211). Targeting this pathway in preclinical models proved successful (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228), although comprehensive human studies are lacking, and the existing limited studies have reported both failures and successes in humans (229). The limitations of the human studies with existing anti-cytokine reagents were recently reviewed in an excellent article (230).…”
Section: Bioactive Lipids and Regulation Of Inflammationmentioning
confidence: 99%
“…A positive correlation between this autonomic dysfunction and the development of type 2 diabetes and cardiovascular disease has been established (12)(13)(14). Accordingly, lowering chronic inflammation, alleviating insulin resistance, and improving autonomic function have been proposed as therapeutic options (11,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The variations in the levels of immune-inflammatory factors have significant implications in the pathophysiology of various diseases such as cancer, obesity, diabetes, fibrosis and atherosclerosis (Meyer et al 2011;Scrivo et al 2011;Ramos-Nino 2013). For these reasons, the role of inflammatory and immune markers in augmenting the therapeutic effect of drugs on chronic inflammation associated diseases (CID) has attracted the attention of researchers (Dinarello 2010;Esser et al 2014). Antiinflammatory agents such as non-steroidal antiinflammatory drugs (NSAIDs) are successfully used in treating CID (Elizabeth et al 2009;Ridker & Lüscher 2014); however, the long-term use of these drugs may result in damage to the gastric intestinal mucosa, heart and kidney (de Groot et al 2007), thereby limiting their usage.…”
Section: Introductionmentioning
confidence: 99%